2011
DOI: 10.1111/j.1728-4457.2011.00379.x
|View full text |Cite
|
Sign up to set email alerts
|

How Much Does Family Matter? Cooperative Breeding and the Demographic Transition

Abstract: P o P u l at i o n a n d d e v e l o P m e n t r e v i e w 3 7 ( S u P P l e m e n t ) : 8 1 -1 1 2 ( 2 0 1 1 ) 8 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
319
3
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 267 publications
(337 citation statements)
references
References 115 publications
13
319
3
2
Order By: Relevance
“…Indeed, we found tentative evidence in the Kaplan Meier plots that by their 30s father absent women may be less likely to have reproduced at all, despite doing so earlier when they do reproduce. This latter finding does not straightforwardly fit the adaptationist approaches above (although we did not measure overall reproductive success of the groups, so neither are our data directly inconsistent with such approaches), but would perhaps be more consistent with evidence from non-Western cultures in which (grand)parental support seems to be an important contributory factor to reproduction (Sear & Coall, 2011).…”
Section: Parental Absence As a Predictor Of Age At First Birthcontrasting
confidence: 57%
See 1 more Smart Citation
“…Indeed, we found tentative evidence in the Kaplan Meier plots that by their 30s father absent women may be less likely to have reproduced at all, despite doing so earlier when they do reproduce. This latter finding does not straightforwardly fit the adaptationist approaches above (although we did not measure overall reproductive success of the groups, so neither are our data directly inconsistent with such approaches), but would perhaps be more consistent with evidence from non-Western cultures in which (grand)parental support seems to be an important contributory factor to reproduction (Sear & Coall, 2011).…”
Section: Parental Absence As a Predictor Of Age At First Birthcontrasting
confidence: 57%
“…Ellis et al, 2003Ellis et al, , 2009; see also Sear & Coall, 2011, for a review). However, given that teen mothers may represent a very particular and small set of individuals (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The idea that there is some basic core in grandparenting gains strong support from the analyses and reviews concerning pre-modern, traditional and contemporary human societies (Sear and Mace 2008;Coall and Hertwig 2010;Sear and Coall 2011) and the fact that the researchers have found occurrence of caring grandmothering for example in many primates furthermore highlights the possibility of the evolutionary value of caring grandparenting (Euler 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies on this is-sue have been conducted in less developed countries and in non-western societies (e.g., Sheppard, Snopkowski & Sear, 2014). Many studies in Western societies have demonstrated the effects of father absence not only on the mortality and health (e.g., Sear & Coall, 2011;Sear & Mace, 2008;Winking, et al, 2009), but also on the reproductive behavior of children (e.g., Alvergne, Faurie & Raymond, 2008;Bogaert, 2008;Mendle et al, 2009;Nettle, Coal & Dickens, 2010). According to life history theory, because of limited resources, individuals have in general to make trade-offs between mating efforts and parenting efforts in order to reproduce (e.g., Chisholm, 1993;Figueredo et al, 2006).…”
Section: The Effects Of Father Absence On Reproductive Strategiesmentioning
confidence: 99%